KORUPSI DALAM PERSPEKTIF HUKUM ISLAM - Hendra Gunawan (Yurisprudentia: Jurnal Hukum Ekonomi, 2018)
The issue and practice of corruption, in fact has happened in the first time only sanya relatively small and in the motive or modest mode even only done by a handful of people, mara historians mentioned that corruption is a sin of the past then in history it is recorded that Rasulullah SAW always do examining or auditing officials who later in the next decade the custom of the Prophet in the later days developed into qadha al-mazhalim (judicial investigative board) in charge of investigating cases relating to Collusion and Nepotism Corruption (KKN). Thus, it can be concluded that in Islamic law corruption is bummed in modern era is not a new case in Islamic law but far long time has been highlighted only sanya terminology is different deang term discussed in Islamic law that is ghulul, risywah, sariqah, and hirabah that will be the author expressed in this paper